2020
DOI: 10.1186/s13287-020-01612-y
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells regulate the Th17/Treg cell balance partly through hepatocyte growth factor in vitro

Abstract: Introduction: Mesenchymal stem cells (MSCs) exert immunomodulatory functions by inducing the development and differentiation of naive T cells into T cells with an anti-inflammatory regulatory T cell (Treg) phenotype. Our previous study showed that hepatocyte growth factor (HGF) secreted by MSCs had immunomodulatory effects in the context of lipopolysaccharide (LPS) stimulation. We hypothesized that HGF is a key factor in the MSC-mediated regulation of the T helper 17 (Th17) cell/regulatory T (Treg) cell balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
4
55
0
2
Order By: Relevance
“…The application of stem cells may also play a part in the protection of the transplanted beta-cells. Such an impact is due to the ability to induce the proliferation of Tregs and the promotion of neovascularization (Caballero et al, 2007;Chen et al, 2020). Thus, a hybrid transplantation, which combined islet transplantation with mesenchymal stem cells, was shown to improve graft function (Figliuzzi et al, 2009).…”
Section: Methods For Beta-cell Preservationmentioning
confidence: 99%
“…The application of stem cells may also play a part in the protection of the transplanted beta-cells. Such an impact is due to the ability to induce the proliferation of Tregs and the promotion of neovascularization (Caballero et al, 2007;Chen et al, 2020). Thus, a hybrid transplantation, which combined islet transplantation with mesenchymal stem cells, was shown to improve graft function (Figliuzzi et al, 2009).…”
Section: Methods For Beta-cell Preservationmentioning
confidence: 99%
“…This effect seems to be partially dependent on IDO, as the impact was less prominent in IDO knock-out MSCs. Novel findings indicated that the inhibition of Th17 cells by murine MSCs is also mediated by HGF ( Chen et al, 2020 ). Furthermore, it has been reported that BM-MSCs impair the IL-17 production by Th17 cells in a contact-dependent manner and induce their interconversion into Tregs ( Luz-Crawford et al, 2019 ).…”
Section: Regulation Of Adaptive Immunity By Mscsmentioning
confidence: 99%
“…Some studies showed that the production of hepatocyte growth factor (HGF) by MSCs can partially modulate the Treg/Th17 balance. An in vitro study using MSC co-cultured in transwell with CD4 + T cells activated with LPS proposed that HGF is necessary for an increased number of CD4 + Foxp3 + cells and a downregulated number of CD4 + RORγt + cells [ 135 ]. In an in vivo model of bronchiolitis obliterans in mice, the infusion of umbilical cord-derived MSCs overexpressing HGF improved the Th1/Th2 ratio, increased the number of Treg cells, and decreased the number of Th17 cells in the spleen; these results were accompanied by decreased IFN-γ levels and increased IL-4 and IL-10 levels in serum [ 136 ].…”
Section: Mechanisms Behind the Msc Immunosuppressive Effect On Th1mentioning
confidence: 99%